2011
DOI: 10.1089/jwh.2010.2192
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intravenous Iron for Treating Postpartum Anemia in Low-Resource African Countries: A Pilot Study in Malawi

Abstract: Our results suggest that IV iron sucrose is an effective drug for treating puerperal anemia, leading to a rapid recovery of Hb levels. The current availability of generic iron sucrose preparations, with considerably lower acquisition costs, may facilitate in-hospital access to this treatment option in low-resource countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…In our study, intravenous ferrous sucrose provided a rapid restoration of both iron stores and Hb for women with postpartum IDA. Similar results had been reported by Asia et al [18], Armand-Ugón et al [19], Bigger et al [20] and Dewan et al [21]. The results of these studies revealed that intravenous therapy significantly increases Hb levels and rapidly replenish iron stores within shortest possible time, i.e.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, intravenous ferrous sucrose provided a rapid restoration of both iron stores and Hb for women with postpartum IDA. Similar results had been reported by Asia et al [18], Armand-Ugón et al [19], Bigger et al [20] and Dewan et al [21]. The results of these studies revealed that intravenous therapy significantly increases Hb levels and rapidly replenish iron stores within shortest possible time, i.e.…”
Section: Discussionsupporting
confidence: 87%
“…Iron sucrose is very effective as it is rapidly removed from plasma and used for Erythropoiesis. These findings are supported by study done by Broche et al (10) in which Hb increase by 1.9gm/dl in 7 days & 3.1 gm/dl in 14 days.…”
Section: Characteristicssupporting
confidence: 82%
“…to increase haemoglobin concentration by 2.1 g dl À1 within 7 days of administration. 209 A comparator group of patients received oral iron supplementation, and these women showed no increase in haemoglobin concentration (possibly because of the short time period). In another study of intravenous iron sucrose, administered preoperatively to patients scheduled for orthopaedic surgery, a significant increase in haemoglobin concentration was observed.…”
Section: Monitoring Therapeutic Interventionsmentioning
confidence: 99%